2014
DOI: 10.1021/ed400468g
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Dispersion Interactions

Abstract: An animation and accompanying activity has been developed to help students visualize how dispersion interactions arise. The animation uses the gecko’s ability to walk on vertical surfaces to illustrate how dispersion interactions play a role in macroscale outcomes. Assessment of student learning reveals that students were able to develop conceptual understanding and accurate mental models of how dispersion interactions arise and their influence on molecular and macroscale outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Muitas das percepções dos especialistas, relacionadas ao caráter universal das interações dispersivas, aditividade das interações, magnitude das energias de interação e a correlação entre parâmetros moleculares e propriedades físico-químicas dos sistemas químicos, estão em conformidade com pesquisas da área de ensino de química (GOTTSCHALK E VENKATARAMAN, 2014;GLAZIER;MARANO;EISEN, 2010;MURTHY, 2006).…”
Section: Considerações Finaisunclassified
“…Muitas das percepções dos especialistas, relacionadas ao caráter universal das interações dispersivas, aditividade das interações, magnitude das energias de interação e a correlação entre parâmetros moleculares e propriedades físico-químicas dos sistemas químicos, estão em conformidade com pesquisas da área de ensino de química (GOTTSCHALK E VENKATARAMAN, 2014;GLAZIER;MARANO;EISEN, 2010;MURTHY, 2006).…”
Section: Considerações Finaisunclassified
“…Observations have shown that by viewing the video, high school students can obtain more detail about the technical aspects of the chemistry laboratory than by listening to the presentations of professional scientists (Burgin et al, 2020). The animation videos have been proven to help students understand complex chemistry topics at the molecular level, such as topics regarding dispersion interactions (Gottschalk & Venkataraman, 2014) and electron transport chain (Wikandari et al, 2021). Video usage in chemistry learning is predicted to grow since the popularity of open-source YouTube videos platform.…”
Section: Introductionmentioning
confidence: 99%
“…Another potentially confusing aspect of dispersion forces is that they are often described in time-dependent language. This is found in almost all textbooks and pedagogical articles; I will give only two examples: "the dynamic, random behavior of the electron cloud may result in a momentary distortion of the symmetric electron distribution, establishing a transient dipole moment" 10 and (in considering the interaction between two well separated hydrogen atoms) "although the hydrogen atom is spherically symmetrical on the average, at any instant the electron is in a position such that the atom has a dipole moment. This instantaneous dipole has a field, and this field tends to polarize the other atom, while the dipole changes, even reverses with high frequency, if the polarization of the other atom keeps phase, the net effect is attractive...".…”
mentioning
confidence: 99%